Elliptic operators and boundary-value problems in spaces of generalized smothness - Mikhailets, V.; Murach, A.; Chepurukhina, I. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.518.2+517.956.22We present a survey of the results obtained for the last ten years in the theory of elliptic boundary-value problems in the Hörmander function spaces developed by the authors, and other related results of modern analysis. The foundations of this theory and some of its applications are systematically presented in the monograph by the first two authors of the survey ``Hörmander spaces, interpolation, and elliptic problems'' (De Gruyter, Berlin/Boston, 2014).